Fertility knowledge and intentions to have children in a national study of Australian secondary school students. (14th August 2016) - Heywood, Wendy; Pitts, Marian K.; Patrick, Kent; Mitchell, Anne
Abstract: Objective: This paper reports on fertility knowledge and intentions to have children among a national sample of students in years 10–12. Method: Data were from the Fifth National Survey of Australian Secondary Students and Sexual Health. Students identified factors that could affect fertility, if they wanted children and at what age. Results: Most students wanted to have children (77%). Of those who wanted children or were unsure (n=1, 780), 54% were able to identify six of eight factors that could affect fertility. Male students had poorer knowledge than females. Poorer knowledge was also reported by male students who were born overseas or used marijuana and by female students who were sexually active or religious. More than half the students (59%) wanted their first child aged 25–29, while 19% wanted their first child after 30. Intentions to have children at an earlier age were associated with being religious, sexually active (females), and using marijuana (males). Students not exclusively attracted to the opposite sex were more likely to want children at an older age. Conclusions and implications: Most students typically want children in their late 20s. Many were unaware of factors that could affect their fertility and there was a mismatch between intentions and likely behaviour. These factors could be addressed as part of relationship education.